Virion Structure of Israeli Acute Bee Paralysis Virus - Mullapudi, Edukondalu; Přidal, Antonín; Pálková, Lenka; de Miranda, Joachim R; Plevka, Pavel (Journal of virology, 2016)
UNLABELLED: The pollination services provided by the western honeybee (Apis mellifera) are critical for agricultural production and the diversity of wild flowering plants. However, honeybees suffer from environmental pollution, habitat loss, and pathogens, including viruses that can cause fatal diseases. Israeli acute bee paralysis virus (IAPV), from the family Dicistroviridae, has been shown to cause colony collapse disorder in the United States. Here, we present the IAPV virion structure determined to a resolution of 4.0 Å and the structure of a pentamer of capsid protein protomers at a resolution of 2.7 Å. IAPV has major capsid proteins VP1 and VP3 with noncanonical jellyroll β-barrel folds composed of only seven instead of eight β-strands, as is the rule for proteins of other viruses with the same fold. The maturation of dicistroviruses is connected to the cleavage of precursor capsid protein VP0 into subunits VP3 and VP4. We show that a putative catalytic site formed by the residues Asp-Asp-Phe of VP1 is optimally positioned to perform the cleavage. Furthermore, unlike many picornaviruses, IAPV does not contain a hydrophobic pocket in capsid protein VP1 that could be targeted by capsid-binding antiviral compounds. IMPORTANCE: Honeybee pollination is required for agricultural production and to sustain the biodiversity of wild flora. However, honeybee populations in Europe and North America are under pressure from pathogens, including viruses that cause colony losses. Viruses from the family Dicistroviridae can cause honeybee infections that are lethal, not only to individual honeybees, but to whole colonies. Here, we present the virion structure of an Aparavirus, Israeli acute bee paralysis virus (IAPV), a member of a complex of closely related viruses that are distributed worldwide. IAPV exhibits unique structural features not observed in other picorna-like viruses. Capsid protein VP1 of IAPV does not contain a hydrophobic pocket, implying that capsid-binding antiviral compounds that can prevent the replication of vertebrate picornaviruses may be ineffective against honeybee virus infections.
Keywords: Models, Molecular; Protein Multimerization; virové struktury; Viral Structures; konformace proteinů; Protein Conformation; virion; krystalografie rentgenová; Capsid Proteins; Dicistroviridae; Crystallography, X-Ray; zvířata; molekulární modely; včely; Virion; Bees; virové plášťové proteiny; Animals; multimerizace proteinu